2016
DOI: 10.1097/scs.0000000000002470
|View full text |Cite
|
Sign up to set email alerts
|

Eosinophilic Granuloma of the Mandible

Abstract: Eosinophilic granuloma is the most benign and common form of the Langerhans cell histiocytosis, a rare proliferative disease that can affect single or multiple organs. In the quite common head and neck manifestation these lesions can be confused in the beginning, with other bone diseases such as odontogenic cysts, periodontal disease, or malignancies. Treatment varies depending on the size, number, localization of the lesions, and patient's general conditions. The authors describe here a patient of a single le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Recurrence rate depends upon the degree of tissue involvement and the treatment method opted; hence, the patient must be monitored closely for a long period . Fiorini et al reported a case with a single EG lesion treated with a very conservative surgical approach with no recurrence during a 2‐year follow‐up period. This approach only consisted of excision of the lesion and curettage of the residual cavity.…”
Section: Discussionmentioning
confidence: 99%
“…Recurrence rate depends upon the degree of tissue involvement and the treatment method opted; hence, the patient must be monitored closely for a long period . Fiorini et al reported a case with a single EG lesion treated with a very conservative surgical approach with no recurrence during a 2‐year follow‐up period. This approach only consisted of excision of the lesion and curettage of the residual cavity.…”
Section: Discussionmentioning
confidence: 99%